Democracy and critique: Comments on Rainer Forst's Justification and Critique: Towards a Critical Theory of Politics. (March 2015) - Chambers, Simone
In this article I challenge Rainer Forst's model of critical theory from the point of view of democratic theory. I suggest that his approach is too abstract and hypothetical to address the real world challenges facing democratic polities today.